A study on incidence of vitamin B12 deficiency in patients with pancytopenia - Kumar, G. Sathish; ., Swetha; Rajendran, V. (International Journal of Advances in Medicine, 2019)
Background: Pancytopenia is a serious and life threatening illness presented with multiple etiologies. The current study was done with the objective to evaluate the clinic-pathological factors responsible for incidence of pancytopenia in patients with vitamin B12 deficiency and their response to the therapy with vitamin B12. Methods: It was an observational study carried out at Department of Medicine, Mahatma Gandhi Memorial Government Hospital, Trichy, Tamilnadu during the period between December 2016 to December 2017. A total 50 patients with pancytopenia were clinically evaluated along with hematological parameters and bone marrow aspiration. Results: A total of 50 patients were included in the study. The mean age of the patients was 32.84 years with a male to female ratio of 1.5:1. All patients had history of fatigability. Commonest physical presentation was pallor (100%). Megaloblastic anaemia was the predominant blood picture in 58% patients. The common bone marrow finding was hyper cellular marrow with megaloblastic picture. Management with cyanocobalamin preparations and folate supplementations, significantly improved the reticulocyte count percentage in patients with pancytopenia (p=0.01) Conclusion: The study concluded that the most common cause of pancytopenia was megaloblastic anaemia. Detailed haematological investigations along with bone marrow aspiration in patients with cytopenia provided a clear understanding of disease process to identify the etiologies of pancytopenia.